HERBAL INGRIDIENTS AS A SOURCE OF ENRICHMENT FOR FLOUR BAKERY PRODUCTS - N. V. Prisuhina; N. A. Grechishikova; A. V. Prisuhin (Современная наука и инновации, 2022)
A lot of various plants with pharmaceutical and therapeutical effects grow in the vast territory of Krasnoyarsk region. Such herbs are hardly used in confectionary, but they are widely used in ethic recipes. The goal of this study is to examine improvement of nutritional quality of product, organoleptic quality indicators and extension of freshness by means of using oregano in flour bakery products. Scones were baked using the standard technology following all technology parameters. Herbal powder was mixed into flour and then we added this blend while kneading the dough. It is established that even with introduction of herbal ingredients of oregano powder the final produce meets requirements of state standards (GOST 15810-2014). Scones gained pleasant taste and herbal flavor, however with increased amount of herbal powder the product's surface became worse and texture turned tougher. In the result of an overall evaluation of samples, the choice was made to a sample with an amount of introduced herbal powder equaled to 5%. This article looks at the possibility of using local herbal pharmaceutical raw materials as an ingredient for flour bakery products. We composed a raw scones recipe with addition of oregano powder. We studied the quality of baked products in correlation to the amount of introduced herbal powder.